Composition tools for contemporary minimalistic architecture - Lupeikis, Kęstutis (Journal of Architecture and Urbanism, 2012)
• Colour, light, shadows. The chapter deals with the role of these compositional means in the minimal expression. They are considered to be the most important means of the minimal composition and they are compared to the idea and space. In the case of the minimal expression, colour is not an adornment but the language of the form. Traditionally, minimalism has been associated with the solutions in grey or white, monochromic colours. However, polychromic minimalism with a prevailing geometrical simplicity in the form and space but with more or less variable polychromic surfaces should not be forgotten either. Light is the most important element in modelling and formation of the space, volume and colour. Light in minimalism is not only the source of lighting but also a compositional means creating a specific meditation mood, exposing textures, transparent structures and the form. A tendency of contemporary architecture is to open the interior spaces of a building to light as much as possible. Shadows make a contrast to light. In a symbolic way, it is considered as the second side, contrary to life, that is necessary to the equilibrium. The soul and vitality are understood as the shadow. It is a very effective means of expression but, like a natural light, it is unstable, makes a movement, creates a specific mood, dematerialises, divides and breaks the form.• Dimension, symmetry–asymmetry, integrity. A dimension in architecture operates as a means of the artistic quality both of the composition and the form. Suggestiveness of the building is often dependent on the size. Tendency of the minimal expression towards reduction or diminishing is a basic one; it is encoded in the very concept of the minimum. However, it is not a physical or direct reduction of the size but rather the purification that makes the concrete form or space empty, seeking to maximally decrease the number of structural elements. A specific rate between the apertures and the plane of the blank wall, typical of the minimal expression, usually changes to the scale of the building. It looks considerably larger, more massive than in reality. Symmetry-asymmetry. It cannot be stated that symmetry or asymmetry is typical of the minimal expression. Though at the first sight it seems that minimalism is characterised by geometry, the right order, and at the same time, by symmetry but we can present a number of examples continuing the asymmetric tradition of the Japanese Zen. Integrity is the most important quality of composition, without integrity we have no composition. In the composition, all elements must be connected into the whole complex. Aiming at the integrity of the composition, the simplest way is to give a geometrical form of the building. Therefore, displaying of geometrical regularities in architecture is one of the forms of artistic expression and a guarantee of the integrity of the composition. Sharpened integrity manifesting itself by blankness of the forms, the monolithic character is a necessary condition for the minimal expression.• Statics–dynamics. In the chapter there are discussed contradictory problems of statics, stability, dynamics and mobility in the contemporary minimal architecture. In architecture, we often observe some sluggishness and static character. The static character is mostly typical of the architecture heritage of ancient civilizations. Dynamism and multi-plane character became distinct as a leading motif in architecture of the 20th century. Essential influence of the dynamics character of contemporary forms, among them also minimal ones is made by the economical and scientifically-technological level of the society, its dynamism, intellectuality and metaphysics. Contemporary architecture is perceived as having not statics but stable form laid out dynamically in the space. In the contemporary context, dynamic models are especially attractive not only due to the fact that they propose flexible means of behaviour in active environments but also because they suggest thinking about lifeless, static forms as being dynamical, alive, changing forms of “life”, interacting with the environment and changing it. When the form of dynamic objects integral, laconic, clean and not overcrowded, then it conforms to the characteristics of the minimal expression. Most often these are not “hand”, angular geometrical forms, these dominate streamline, plastic surfaces that make the image of impetuosity, mobility and spinning. It is proven that the minimal form in the contemporary architecture may be not only static but also dynamic.Article in Lithuanian.Kompozicinės priemonės šiuolaikinėje minimalistinėje architektūrojeSantrauka. Be formos neįmanoma jokia architektūra, o minimalizmo atveju ji yra išskirtinai specifiška, vis dėlto minimalistinės raiškos pobūdį stipriai veikia įvairios kompozicinės priemonės. Straipsnyje aptariami įvairūs, siejami su minimalistine raiška, kompozicinių priemonių panaudojimo aspektai. Analizuojant architektūrinius objektus, daug kas priklauso nuo jų spalvinio pobūdžio, šviesos, šešėlių žaismo panaudojimo, jų masto, simetriškumo ar asimetrijos, vientisumo ar daugialypiškumo, nuo to, ar turima galvoje dinamiška gyvybės forma, atvira išorinėms įtakoms, ar statiškas objektas.Visuotinai yra susiformavę tam tikri minimalistinės raiškos stereotipai, pvz.: kad minimalistinei architektūrai yra būdinga balta spalva ar bent jau achromatiniai tonai (pilka, juoda), smulkumas, simetrija ir statika. Šiame straipsnyje siekiama paneigti minėtus stereotipus, pateikiant spalvingojo minimalizmo, asimetrinių ir dinamiškų minimalistinių architektūros objektų pavyzdžius, be to, atskleidžiamas jų tūrių masės ir vientisumo charakteris, šviesos ir šešėlių kompozicinė svarba.Reikšminiai žodžiai: minimalizmas, kompozicija, kompozicijos priemonės, spalva, šviesa, šešėlis, mastas, simetrija, asimetrija, vientisumas, statika, dinamika.